CHILDREN WITH CYSTIC FIBROSIS: UNDERSTANDING ISSUES RELATED TO ORAL ADMINISTRATION OF LIQUID FLUCLOXACILLIN. Issue 9 (17th August 2016) - Batchelor, Hannah; Rayner, Oli; Nickless, Jessica; Wan, Mandy; Southern, Kevin; Rose, Claudia
Abstract : Aim: Palatability of flucloxacillin is poor, yet is used long-term in the management of children with cystic fibrosis (CF). Strategies to aid administration of unpalatable medicines have been reported, however there has never been a systematic approach to gathering views of many parents/carers all administering the same medication to the same population of children. This study aimed to quantify the extent of flucloxacillin palatability issues for parents/cares of children with CF and identify parent/carer and healthcare professional (HCP) reported age-specific strategies to aid administration of flucloxacillin to children with CF. Method: Passive analysis reviews of public online forums were conducted using search terms including, 'flucloxacillin' and 'taste' or 'palatability' or 'child' to identify evidence of tactics used by parents to aid administration of flucloxacillin to children, not only those with CF (strategies were only included if the age of the child was disclosed). A bespoke online questionnaire was developed and partially validated for parents/carers of children with CF to identify age-specific strategies to aid administration of flucloxacillin. Healthcare professionals (HCPs) were purposively selected for semi-structured interviews to further explore age-specific strategies to aid administration of flucloxacillin. Results: 18 individual strategies were identified on 10 different public online forums to aid the administration of flucloxacillin to children. These included mixing with food/drink: milk was commonly used for children aged 6–20 months; honey, Nutella, jam, ice cream and squash for those aged 21–36 months. The use of an oral syringe to direct the medicine slowly into the back/side of the mouth, and pinching a child's nose was reported. 253 parents/carers of children with CF completed the online survey and 11 HCPs were involved in the semi-structured interviews. 50.2% of parents/carers reported that administration of flucloxacillin was problematic, yet 89.3% reported that they administered 'most' or 'all doses' of flucloxacillin. 90.5% of parents/carers found administration of flucloxacillin more problematic than other medicines in pre-weaned babies. 162 of 253 parents/carers chose to comment on ways that administration of flucloxacillin could be improved/eased, with 38.3% of these respondents suggesting improved palatability was necessary. Mixing with food/drink was rarely reported by parents/carers of children with CF (15.9%) or HCPs (27.3%), contrary to data identified within online forums. This difference highlights that parents of children with CF are less likely to use food to aid administration compared to those using flucloxacillin for acute infections. A multi-methods approach to obtain information on manipulation of medicines by parents/carers would provide greater insights into explaining this finding. Conclusion: The results from this study showed that flucloxacillin is unpalatable and that parents/carers use a range of strategies to improve acceptability of this product. Although food is an obvious strategy for making flucloxacillin more palatable when treating an acute infection; it may be that this doesn't work in longer term therapy (eg CF) and the wider population can learn from parents/carers with more experience with this medicine. Parents of children with CF and HCPs have provided useful age-specific strategies to ease administration of the known poorly tolerated medicine, liquid flucloxacillin.